Phytochemistry, Pharmacology and Toxicology of Spilanthes acmella: A Review - Suchita Dubey; Siddhartha Maity; Mahendra Singh; Shubhini A. Saraf; Sudipta Saha (Advances in Pharmacological Sciences)
Spilanthes acmella is an important medicinal plant, found in tropical and subtropical countries mainly India and South America. Popularly, it is known as toothache plant which reduces the pain associated with toothaches and can induce saliva secretion. Various extracts and active metabolites from various parts of this plant possess useful pharmacological activities. Literature survey proposed that it has multiple pharmacological actions, which include antifungal, antipyretic, local anaesthetic, bioinsecticide, anticonvulsant, antioxidant, aphrodisiac, analgesic, pancreatic lipase inhibitor, antimicrobial, antinociception, diuretic, vasorelaxant, anti-human immunodeficiency virus, toothache relieve and anti-inflammatory effects. This review is elaborately describing the traditional uses, phytochemistry, pharmacology, and toxicology of this plant. This review would assist researchers to search scientific information in the future.